The development of academic information system (case study: Santa Maria 3 Malang kindergarten school) - Tansa Wiguna; Hendro Poerbo Prasetiya (Universitas Muhammadiyah Magelang, 2022)
Kindergarten Santa Maria 3 Malang uses manual performance with excel in its current operations, so it is constrained by data that is not the same because it uses a non-centralized file, formulas, or formulas to generate values that are often deleted. Academic applications are needed to reduce the time to adapt to the grading system and assist teachers in improving student services outside of academics. The application is built on a website base that is responsive to the device used. So that it can be accessed at any time, besides that centralized data helps teachers in collecting or searching data quickly and precisely. The system is made and developed according to the directions and processes that exist in the Santa Maria 3 Kindergarten Malang environment. So that this journal will discuss more clearly the process of making an academic information system for Santa Maria 3 Kindergarten Malang.